Sustainability Product Portfolio: A Review - Villamil, Carolina; Hallstedt, Sophie I. (European Journal of Sustainable Development, 2018)
Many companies have identified the importance of sustainable innovation for long-term competitiveness and recognition but face difficulties in translating sustainability strategies into practical action. Some companies have shown an interest to include sustainability dimensions into their product portfolio, which can be an efficient way to communicate the sustainability performance of the products internally and externally and even speed up the development of more sustainable solutions. Our research aims to determine how a sustainability portfolio can be defined and how to assess portfolios from a sustainability perspective. A systematic literature review on sustainability product portfolio was conducted. The results indicated that a general portfolio setting follows a selection criteria and the company´s strategies, which usually are based on management elements, e.g., time, cost, risk, quality, etc., leaving behind sustainability variables. Most of the tools used for evaluation criteria miss the holistic view. The companies could benefit from a systematic approach to implementing sustainability into their product portfolio. The findings were connected with a previous study to evaluate a sustainability assessment approach used for a technology portfolio. For future work, a descriptive study will complement an understanding on how to guide companies to shape their sustainability product portfolios. Keywords: Sustainable product development, sustainability portfolio, product planning, portfolio management, product portfolio